Penerapan Senam Kaki terhadap Diabetic Sensorymotor Polyneuropathy dan Gula Darah Sewaktu pada Penderita Diabetes Melitus - Mona Destriana; Sanny Frisca; Veroneka Yosefpa Windahandayani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Diabetic Sensorimotor Polyneuropathy (DSPN) is a common chronic complication of diabetes mellitus caused by persistent hyperglycemia, resulting in sensory, motor, and autonomic nerve damage, particularly in the lower extremities. DSPN increases the risk of diabetic foot ulcers, infections, and amputations. Previous studies by Astuti and Ritonga showed that diabetic foot exercises can improve peripheral neuropathy and reduce blood glucose levels. To evaluate the effect of diabetic foot exercises on DSPN and random blood glucose (RBG) levels in patients with diabetes mellitus. This evidence-based practice (EBP) implementation involved three patients with diabetes mellitus. Random blood glucose was measured using a glucometer, while DSPN was assessed using the Neuropathy Symptom Score (NSS) and Neuropathy Disability Score (NDS). Foot exercises were performed twice daily for four consecutive days following the standard operating procedure. All respondents showed decreased RBG levels. Nursing assessment identified unstable blood glucose levels, ineffective peripheral tissue perfusion, and deficient knowledge regarding a healthy lifestyle. The average RBG reduction was 12.8%, with improved NSS and NDS scores. After four days, all respondents demonstrated lower RBG levels and improved DSPN status. Diabetic foot exercise may serve as an effective complementary nursing intervention to improve glycemic control and peripheral nerve function.